Impact of m6A modification and transcript quantity on mRNA composition in plant stress granules under hypoxia - Kubiak, Dawid Jakub; Szcześniak, Michał Wojciech; Ostrowska, Karolina; Bielewicz, Dawid; Bhat, Susheel Sagar; Niedojadło, Katarzyna; Szweykowska-Kulińska, Zofia; Jarmołowski, Artur; Fray, Rupert George; Niedojadło, Janusz (Journal of experimental botany, 2025)
Stress granules (SGs) are cytoplasmic structures that appear in response to unfavorable environmental conditions. The mechanisms governing the accumulation of transcripts in SGs are only partially understood, and despite the recognized role of N6-methyladenosine (m6A) in plant transcriptome regulation, its impact on SG composition and assembly remains unknown. In Lupinus angustifolius, SGs display a distinctive bi-zonal structure comprising of a ring and a central area with differences in their ultrastructure and composition. Following a transcriptome analysis, specific mRNAs were chosen to investigate their localization within SGs and to assess m6A levels. Transcripts of hypoxia-responsive genes (ADH1 and HUP7) showed significantly lower levels of m6A compared to housekeeping genes, but only ADH1 was absent in SGs. HUP7 mRNA, characterized by a low quantity of m6A, was present both in the SGs and the cytoplasm, probably due to an extremely high expression level. The m6A modification was observed only during the assembly of SGs. In mutants of Arabidopsis with reduced levels of m6A, ECT2 (a reader of m6A) was not observed in SGs, and poly(A) RNA levels and the number of SGs were reduced. Our findings thus demonstrate a limited impact of m6A modification on SG assembly; however, the interplay between m6A modification and the overall transcript quantity in the cytoplasm appears to play a regulatory role in mRNA partitioning and assembly of SGs.